2021
DOI: 10.3389/fphar.2021.809541
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Fluoxetine and Vortioxetine in a Non-Transgenic Animal Model of Alzheimer’s Disease

Abstract: Depression is a risk factor for the development of Alzheimer’s disease (AD). A neurobiological and clinical continuum exists between AD and depression, with neuroinflammation and oxidative stress being involved in both diseases. Second-generation antidepressants, in particular selective serotonin reuptake inhibitors (SSRIs), are currently investigated as neuroprotective drugs in AD. By employing a non-transgenic AD model, obtained by intracerebroventricular (i.c.v.) injection of amyloid-β (Aβ) oligomers in 2-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 84 publications
(104 reference statements)
2
29
0
Order By: Relevance
“…It has also been demonstrated that wounded tissues are characterized by elevated oxidative stress, presenting high levels of MDA paralleled by decreased levels of antioxidants [56,59,60]. Second-generation antidepressants, such as FLX, are also known to exert an antioxidant activity both in vitro and in vivo [22,61]. Based on the evidence described above, we investigated the tissue levels of MDA, GSH, SOD, and GPx in diabetic rats subjected to our different experimental conditions.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has also been demonstrated that wounded tissues are characterized by elevated oxidative stress, presenting high levels of MDA paralleled by decreased levels of antioxidants [56,59,60]. Second-generation antidepressants, such as FLX, are also known to exert an antioxidant activity both in vitro and in vivo [22,61]. Based on the evidence described above, we investigated the tissue levels of MDA, GSH, SOD, and GPx in diabetic rats subjected to our different experimental conditions.…”
Section: Discussionmentioning
confidence: 97%
“…Hence, serotonin, or selective serotonin reuptake inhibitors (SSRIs), have been examined to promote wound healing in experimental models [20]. Fluoxetine (FLX), the first antidepressant developed in the class of the SSRIs, represents one of the main first-line medications used for major depression, and is also known to reduce inflammation [21] and oxidative stress [22]. FLX, administered intraperitoneally, has also been shown to be able to enhance the wound healing process in chronically stressed Wistar rats [23].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous preclinical and clinical studies have further suggested that the consumption of dietary antioxidants such as ascorbic acid, tocopherol, beta-carotene, polyphenols, isoflavonoids, and omega-3 polyunsaturated fatty acids significantly improves depressive symptoms in patients [ 58 , 59 , 60 , 61 ]. Indeed, conventional antidepressant medications including doxepin, fluoxetine, and vortioxetine endowed with oxidative and nitrosative scavenging activities have a protective effect [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is continually increasing evidence that inflammation [ 45 , 46 , 47 ], oxidative stress [ 48 , 49 , 50 ], and aberrant aggregation and accumulation of proteins [ 51 , 52 ] significantly contribute to numerous systemic and neurodegenerative disorders such as diabetes mellitus type 2 (T2DM) [ 53 , 54 ], PD [ 55 , 56 ], and AD [ 57 , 58 , 59 ]. In this context, the well-known and frequently cited anti-oxidant, anti-inflammatory, and anti-aggregant activities of carnosine, which underline its multimodal mechanism of action, have been considered.…”
Section: The Multimodal Mechanism Of Action Of Carnosine: Contributio...mentioning
confidence: 99%